Preface - Bernoth, Jan; Goth, Florian; Lamprecht, Anna-Lena; Linxweiler, Jan (Electronic Communications of the EASST, 2025)
We are pleased to present the proceedings of the 4th Conference for Research Software Engineering in Germany, hosted in 2024 by the Faculty of Physics and Astronomy of the University of Würzburg. 22 papers were submitted in response to our call for contributions to this post-proceedings volume, and 18 of those were finally accepted for publication. All accepted contributions are published in this diamond open-access journal, ensuring free access for both authors and readers while maintaining rigorous academic quality. We hope these proceedings serve as both a valuable reference, and an inspiration for further innovation and collaboration in Research Software Engineering.